Composition Analysis of Municipal Solid Waste A Case Study in Benghazi, Libya - Faisal Ali Mohamed Baba; Miraç Aydın; Idris Imneisi (Turkish Science and Technology Publishing (TURSTEP), 2018)
Benghazi, like other cities in Libya, faces problems associated with poorly managed solid waste operation. The uncertainty of the types of municipal solid waste (MSW) it is the challenge that, hinders chosen the best method for solid waste management. This study deals composition analysis of the city’s MSW as, sustainable waste management options. To specify types of MSW the samples collection in wet seasons and dry seasons. Number of samples collected as 40 samples per season. And to get a representative sampling, in this case employed a range of sampling techniques including stratified sampling, systematic random sampling, and purposive sampling. The samples was collected, mixed and then weighed as, kilogram (Kg). The samples were characterized. as, paper, glass, metals, plastics, textiles, non-food, food and putrescibles, misc-combustibles, misc. non-combustibles, household hazardous waste. And then the samples weighed again to determine the proportion of each type. Finally, this study forwarded some important conclusion and recommendations towards improving the current situation.
Keywords: S; Agriculture (General); Municipal solid waste; Benghazi; Agriculture; Libya; S1-972; Composition; 6. Clean water; 12. Responsible consumption; 13. Climate action; 11. Sustainability